Can the surgical tourniquet be used in patients with sickle cell disease or trait? A review of the literature. Issue 2 (1st February 2017) - Pignatti, Marco; Zanella, Sara; Borgna-Pignatti, Caterina
ABSTRACT: Introduction: In patients with sickle cell disease, circulatory stasis, acidosis, and hypoxemia induce red cell deoxygenation and consequent sickling. Tourniquets are an important adjunct in limb surgery to obtain a bloodless field. Many local and systemic effects, due to the inflation and deflation of the tourniquet, can develop. These effects may have severe consequences if comorbidities are present. The use of a tourniquet in sickle cell patients is controversial because it may provoke vaso-occlusive complications. Areas covered: We reviewed the literature to detect reports of the use of tourniquet in sickle cell disease or sickle trait. We found only three case reports and five case series, three of which controlled, none randomized, on the complications of tourniquet. Expert commentary: From what we could find in the literature and contrary to what is suggested by most guidelines it appears that complications are rare. However, caution must be applied and the risk/benefit ratio carefully considered.